2021
DOI: 10.30827/pna.v15i2.16155
|View full text |Cite
|
Sign up to set email alerts
|

Educación matemática en países hispanohablantes: evolución de su documentación de acceso abierto

Abstract: Estudiamos la evolución de la Educación Matemática en países de habla his- pana. Analizamos el contenido de documentos de acceso abierto a partir de categorías que emergen de una taxonomía de términos clave específica para la disciplina. Determinamos el comportamiento diacrónico de la documenta- ción y su especialidad temática en relación con niveles educativos, contenido matemático y nociones pedagógicas. Los resultados evidencian el crecimiento exponencial de la producción… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
1
1
0
1
Order By: Relevance
“…We see that the community that converges in the meeting is more interested in the theoretical development associated with geometry than in the generation of practical proposals that can be taken to the classroom. The interest observed in the dissemination of research work compared to other types of work is consistent with what is observed in the Ibero-American community and shows the trend towards the systematic formalization of stances related to mathematics education (Castro & Gómez, 2021).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…We see that the community that converges in the meeting is more interested in the theoretical development associated with geometry than in the generation of practical proposals that can be taken to the classroom. The interest observed in the dissemination of research work compared to other types of work is consistent with what is observed in the Ibero-American community and shows the trend towards the systematic formalization of stances related to mathematics education (Castro & Gómez, 2021).…”
Section: Discussionsupporting
confidence: 83%
“…The visibility of knowledge in mathematics education, as far as the Ibero-American community is concerned, tends to be similar in terms of the number of articles published in journals and the number of contributions to meetings in national and international meetings (Castro & Gómez, 2021;Molina et al, 2011). However, few studies have been developed on the knowledge dissemination media, so they merit further research Maz-Machado et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Existen oportunidades para estudiar de manera más amplia el comportamiento de la investigación y la innovación en un campo del conocimiento a nivel internacional. En el caso de la Educación Matemática, identificamos oportunidades para caracterizar este comportamiento en los países de habla hispana de acuerdo con el crecimiento de su producción documental (Castro y Gómez, 2021).…”
Section: Conclusionesunclassified